Revenue and water production records from seven rural piped water service providers, 2016-2020 - Armstrong, A (University of Oxford, 2023)
This dataset has been compiled from secondary, longitudinal records maintained by seven agencies that operate piped water services in rural areas of ten countries. Three of the agencies are international nongovernmental organisations that operate as social enterprises. Three agencies are private companies that offer a range of engineering, construction, and management services. One agency is a public utility.